Peningkatan Keterampilan Menulis Teks Eksplanasi pada Pembelajaran Bahasa Indonesia Menggunakan Model Problem Based Learning di Kelas V SDN 18 Tangahkoto Kabupaten Agam - Irgandi, Indah; Suriani, Ari; Alwi, Nur Azmi; Muhammadi, Muhammadi (Darul Yasin Al Sys, 2025)
This study is motivated by field observations showing that students' writing skills are low due to the lack of learning activities that engage students, as the learning process is still teacher-centered. As a result, students remain passive during the learning process. This study aims to describe how the implementation of the Problem-Based Learning (PBL) model can improve students' writing skills in Indonesian language learning, specifically on explanation text material, in grade V at SDN 18 Tangahkoto, Agam District.This research is a classroom action research (CAR) using both qualitative and quantitative approaches. The study was carried out in two cycles, with research procedures consisting of planning, implementation, observation, and reflection. The data collected relate to writing skills using the Problem-Based Learning model. Data collection techniques included tests and non-tests. The subjects of this research were the class teacher as the observer, the researcher as the practitioner or teacher, and the fifth-grade students of SDN 18 Tangahkoto, Agam District, totaling 20 students. The results of the study show that: First, the teaching module in cycle I achieved an average of 85.93% (B), which increased to 96.87% (SB) in cycle II. Second, the teacher's performance in cycle I showed an average of 83.92% (B), which improved to 96.42% (SB) in cycle II. Meanwhile, the students' performance in cycle I averaged 80.35% (C), which increased to 96.42% (SB) in cycle II. Third, the students' writing skill assessment in cycle I showed an average of 71 (K), which increased to 83 (B) in cycle II. Therefore, it can be concluded that the Problem-Based Learning (PBL) model can improve students' writing skills in explanation texts in Indonesian language learning for fifth-grade students at SDN 18 Tangahkoto, Agam District.